Investigation on the behaviors of water infiltration in the unsaturated loess - Xi, Yu; Hua, Xue-Qing; Li, Gang; Wang, Peng-Zhou; Yang, Sha-Sha (Frontiers in Earth Science, 2024)
Introduction: Surface water from precipitation or irrigation is the sole contributor to groundwater replenishment in the Loess Plateau of China. The occurrence of landslides in the Loess Plateau is closely related to the infiltration process of surface water, and the frequent occurrence of landslides in the Loess Plateau in recent years has seriously affected the economic development and security of the Loess Plateau. Methods: To investigate the loess infiltration in deeper soil, the process of moisture infiltration in unsaturated loess is studied by field observation, theoretical analysis, and numerical simulation. Results and discussion: The research results indicated that the interstitial flow in loess could be divided into three different zones: the active zone, the stable zone (2–94 m), and the saturated zone (below 97 m); based on the matric suction and water content calculations, the L1 soil stable water content is 24.4%, which corresponds to the moisture sensor measurement of L1 loess 4 m and 7 m of stable zone data; the numerical simulation results show that whether the infiltration is continuous or intermittent, the infiltration law is the same. After 20 years, there will be a stable water content zone in the 1–8 m soil layer with a water content of 31%. The numerical results well confirm the theoretical calculation results. The research results explain the process of surface water infiltration into groundwater through thick loess and can provide an important reference for the prevention and control of geological disasters caused by water infiltration in loess areas.